Reduced Sensitivity to Anesthetic Agents upon Lesioning the Mesopontine Tegmental Anesthesia Area in Rats Depends on Anesthetic Type. (March 2020) - Minert, Anne; Baron, Mark; Devor, Marshall
Abstract : Background: The brainstem mesopontine tegmental anesthesia area is a key node in circuitry responsible for anesthetic induction and maintenance. Microinjecting the γ-aminobutyric acid–mediated (GABAergic) anesthetic pentobarbital in this nucleus rapidly and reversibly induces general anesthesia, whereas lesioning it renders the animal relatively insensitive to pentobarbital administered systemically. This study investigated whether effects of lesioning the mesopontine tegmental anesthesia area generalize to other anesthetic agents. Methods: Cell-selective lesions were made using ibotenic acid, and rats were later tested for changes in the dose–response relation to etomidate, propofol, alfaxalone/alfadolone, ketamine, and medetomidine delivered intravenously using a programmable infusion pump. Anesthetic induction for each agent was tracked using five behavioral endpoints: loss of righting reflex, criterion for anesthesia (score of 11 or higher), criterion for surgical anesthesia (score of 14 or higher), antinociception (loss of pinch response), and deep surgical anesthesia (score of 16). Results: As reported previously for pentobarbital, on-target mesopontine tegmental anesthesia area lesions reduced sensitivity to the GABAergic anesthetics etomidate and propofol. The dose to achieve a score of 16 increased to 147 ± 50% of baseline in control animals ± SD ( P = 0.0007; 7 lesioned rats and 18 controls) and 136 ± 58% of baseline ( P = 0.010; 6 lesioned rats and 21 controls), respectively. In contrast, responsiveness to the neurosteroids alfaxalone and alfadolone remained unchanged compared with baseline (94 ± 24%; P = 0.519; 6 lesioned rats and 18 controls) and with ketamine increased slightly (90 ± 11%; P = 0.039; 6 lesioned rats and 19 controls). The non-GABAergic anesthetic medetomidine did not induce criterion anesthesia even at the maximal dose tested. The dose to reach the maximal anesthesia score actually obtained was unaffected by the lesion (112 ± 8%; P = 0.063; 5 lesioned rats and 18 controls). Conclusions: Inability to induce anesthesia in lesioned animals using normally effective doses of etomidate, propofol, and pentobarbital suggests that the mesopontine tegmental anesthesia area is the effective target of these, but not necessarily all, GABAergic anesthetics upon systemic administration. Cortical and spinal functions are likely suppressed by recruitment of dedicated ascending and descending pathways rather than by direct, distributed drug action. Abstract : Targeted microinjection of ibotenic acid into the mesopontine tegmental anesthesia area in adult rats led to an up to twofold loss in anesthetic potency of etomidate and propofol. In contrast, the potency of ketamine, medetomidine, and alfaxolone/alfadolone were unaffected. These observations suggest that the mesopontine tegmental anesthesia area of the brainstem may serve as a key structure to selectively mediate transition from wakefulness into an anesthetic state in response to γ-aminobutyric acid–mediated anesthetics.Supplemental Digital Content is available in the text.